EVOLUTION OF EXOGENE COPPER ACCUMULATION IN EARTH HISTORY - Lur'ye A.M. (My University, 1989)
The evolution of exogene copper accumulation can be illustrated by cupriferous sandstones and shales, which are known from the Early Proterozoic to the Neogene, inclusive. Their exogene origin throughout that time interval is proved by their constant relationship to a certain sedimentary rock association, the arid red-bed. Processes that produced ore deposits of different age always resulted in removal of copper from red beds by ground water, followed by its precipitation at geochemical barriers. Therefore, in this article it is considered how the conditions under which the parent rocks of cupriferous sandstone and shale were formed have changed with time.
Keywords: Proterozoic; Neogene; Кайнозой::Неоген; Cenozoic::Neogene; Precambrian::Proterozoic; Докембрий::Протерозой